New Alignment Method Using Hydraulic Jack for Accelerating SWD 16 TM 410 R Engine and Generator Coupling - Nugroho, Satriyo Dwi; Fajriannur, Fajriannur (Department of Mechanical and Industrial Engineering, 2024)
In 2019, the #6 PLTD Trisakti SWD (Stork Werkspoor Diesel) 16 TM 410 R underwent critical engine rehabilitation due to severe issues that had persisted since 2018. The rehabilitation necessitated the replacement of the crankshaft and bedplate. Given the engine and generator positioning adjustments, an alignment process was crucial to ensure correct realignment. Subsequently, the comprehensive rehabilitation efforts, containing alignment and engine-generator coupling, were concluded in March 2021. A misalignment issue was identified during the running test program as the generator shaft exhibited an imbalance. A realignment process and reattachment of fitted bolts were considered necessary to rectify this imbalance. The previous approach for this task demanded an extensive 54-day timeframe without a guaranteed resolution. This paper will discuss a breakthrough method for shaft alignment. By applying this new method, the alignment focus is directly at the point of the farthest deviation, compared to the previous method, which had to look for the midpoint of the x and y arcs. So that the alignment process can be carried out quickly and precisely. Apart from that, this innovation also proposes a new reaming method using line boring. This tool works more effectively than hand reaming, which requires more time and manpower. This innovation achieved an exceptional 81% reduction in processing time, concurrently leading to a significant decrease in the requisite workforce.